Acentrosomal Microtubule Assembly in Mitosis: The Where, When, and How. Issue 2 (February 2016) - Meunier, Sylvain; Vernos, Isabelle
Abstract : In mitosis the cell assembles the bipolar spindle, a microtubule (MT)-based apparatus that segregates the duplicated chromosomes into two daughter cells. Most animal cells enter mitosis with duplicated centrosomes that provide an active source of dynamic MTs. However, it is now established that spindle assembly relies on the nucleation of acentrosomal MTs occurring around the chromosomes after nuclear envelope breakdown, and on pre-existing microtubules. Where chromosome-dependent MT nucleation occurs, when MT amplification takes place and how the two pathways function are still key questions that generate some controversies. We reconcile the data and present an integrated model accounting for acentrosomal microtubule assembly in the dividing cell. Trends: Bipolar spindle formation relies on various MT assembly pathways, some of them independent on centrosome activity. The main acentrosomal MT assembly pathways are RanGTP-dependent, kinetochore (CPC)-dependent, and augmin-dependent pathways. RanGTP is generated by the chromosomes, and triggers MT nucleation de novo . The kinetochore acts as a hot-spot for MT stabilization, and promotes MT assembly and K-fiber formation. The augmin pathway induces MT nucleation and branching from a pre-existing MT. The RanGTP and the augmin pathways may act sequentially to promote acentrosomal MT assembly in mitosis. Chromosomal MTs initiate K-fiber formation and define their dynamic properties.